Conjugated Ladder Polymers by a Cyclopentannulation Polymerization - Bheemireddy, Sambasiva R; Hautzinger, Matthew P; Li, Tao; Lee, Byeongdu; Plunkett, Kyle N (Journal of the American Chemical Society, 2017)
We report a nontraditional synthesis of cyclopentafused-polycyclic aromatic hydrocarbon embedded ladder polymers using a palladium catalyzed cyclopentannulation polymerization followed by a cyclodehydrogenation reaction. Donor–acceptor type polymers containing a cyclopenta[hi]aceanthrylene acceptor groups can be synthesized by a palladium catalyzed copolymerization between 9,10-dibromoanthracene and a variety of bis(arylethynyl)arenes to give polymers with molecular weights (Mn) of 9–22 kDa. The bis(arylethynyl)arenes were composed of benzene, thiophene, or thieno[3,2-b]thiophene moieties, which provided access to a series of four donor–acceptor copolymers. The polymers were subjected to cyclodehydrogenation with FeCl3 to access rigid ladder type polymers with the conversion investigated by 13C NMR of isotopically labeled polymers. The ladder polymers possess broad UV–Vis absorptions and narrow optical band gaps of 1.17–1.29 eV and are p-type semiconductors in organic field effect transistors.